Differential protection scheme for a micro grid with inverter-type sources based on positive sequence fault currents - Alhadrawi, Zaid (Penerbit UTHM, 2022)
The microgrid (MG) is a coordinated collection of different distributed generation (DG) types that supply local demand through a distribution network. MG may operate in two different modes: grid-connected (GC), and islanded (IS) modes. The fault current value varies significantly between the GC and IS mode for a MG with inverter-based distributed generators (IBDGs). The fault currents are minimal in the IS mode owing to the power electronics equipment have a limited current carrying capacity. Therefore, the coordination of traditional overcurrent (OC) protection is difficult for these two operation modes. Therefore, a comprehensive MG protection scheme should be established to safeguard MG against all kinds of faults. The main protection strategy proposed in this paper is a positive sequence differential current protection scheme. The envisioned concept can overcome the protective device coordination problems, and all fault types can be detected during both operation modes of MG for radial and loop configurations. The validation of the proposed design is performed using PSCAD/EMTDC software. The results indicate that the maximum fault clearing time for the main protection in GC mode and IS mode is of 31.5 ms and 34 ms respectively. Compared with other schemes, the proposed scheme has a faster clearing time and is less expensive. © Universiti Tun Hussein Onn Malaysia Publisher’s Office